Protected areas offer refuge from invasive species spreading under climate change - Gallardo, Belinda; Aldridge, David C.; González‐Moreno, Pablo; Pergl, Jan; Pizarro, Manuel; Pyšek, Petr; Thuiller, Wilfried; Yesson, Christopher; Vilà, Montserrat (Global change biology, 2017)
Protected areas (PAs) are intended to provide native biodiversity and habitats with a refuge against the impacts of global change, particularly acting as natural filters against biological invasions. In practice, however, it is unknown how effective PAs will be in shielding native species from invasions under projected climate change. Here, we investigate the current and future potential distributions of 100 of the most invasive terrestrial, freshwater, and marine species in Europe. We use this information to evaluate the combined threat posed by climate change and invasions to existing PAs and the most susceptible species they shelter. We found that only a quarter of Europe's marine and terrestrial areas protected over the last 100 years have been colonized by any of the invaders investigated, despite offering climatically suitable conditions for invasion. In addition, hotspots of invasive species and the most susceptible native species to their establishment do not match at large continental scales. Furthermore, the predicted richness of invaders is 11%–18% significantly lower inside PAs than outside them. Invasive species are rare in long‐established national parks and nature reserves, which are actively protected and often located in remote and pristine regions with very low human density. In contrast, the richness of invasive species is high in the more recently designated Natura 2000 sites, which are subject to high human accessibility. This situation may change in the future, since our models anticipate important shifts in species ranges toward the north and east of Europe at unprecedented rates of 14–55 km/decade, depending on taxonomic group and scenario. This may seriously compromise the conservation of biodiversity and ecosystem services. This study is the first comprehensive assessment of the resistance that PAs provide against biological invasions and climate change on a continental scale and illustrates their strategic value in safeguarding native biodiversity. Protected areas are championed as refugia for native biodiversity and habitats, but we do not know how effective they are in shielding native taxa from biological invasions under projected climate change. Here, we found that only a quarter of Europe's marine and terrestrial areas protected over the last 100 years have been colonized by 100 of the worst terrestrial, freshwater, and marine invaders, with long‐established areas showing the lowest richness of invaders (A). This situation may change in the future, as models anticipate a shift in species distribution toward the north and east of Europe in response to climate change (B).